Meningeal sarcoidosis, pseudo-meningioma, and pachymeningitis of the convexity. Issue 4 (April 1992) - Ranoux, D; Devaux, B; Lamy, C; Mear, J Y; Roux, F X; Mas, J L
Abstract : Two cases of meningeal sarcoidosis with unusual and misleading presentations are reported. In the first case, CT scan, angiographic, and MRI findings were indistinguishable from those of meningioma. CSF pleiocytosis may help in diagnosing sarcoid pseudo-meningioma. The second patient had transient focal deficits and pachymeningitis of the convexity. The transient deficits were probably of epileptic origin based on their response to antiepileptic treatment. The diagnosis of neurosarcoidosis was made only after meningeal biopsy, despite thorough investigations.